Radiobiology in brachytherapy - Żyromska, Agnieszka; Makarewicz, Roman (Contemporary Oncology/Współczesna Onkologia, 2009)
Due to the unique physical characteristics of brachytherapy the radiobiological principles which are obligatory in radiotherapy acquire individual features with reference to particular irradiation techniques using radioactive sources and should be taken into account in clinical practice. Additionally, the progressive development of knowledge on cancer biology, especially on post-irradiation repair phenomena, presents the issue of biological effects of all brachytherapy techniques in a new light today. In the article we discuss the radiobiological characteristics of brachytherapy methods, relating to established dogmas and analysing them in the context of the latest results of studies on the biological profile of cancers and normal tissues. We point out differences between biological effects of brachytherapy and external beam irradiation as well as resulting changes in relevant mathematical models.